A modified resin and a method for preparing the same
Patent Information
- Application Number
- CN202611240939.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-30
AI Technical Summary
然而,该技术方案仍存在以下不足:(1)树脂基体自身内聚强度有限,在高温高盐环境下易老化降解;(2)缺乏无机刚性骨架支撑,抗冲击性和尺寸稳定性不足;(3)对砂粒表面的多点锚定作用存在官能团饱和效应,性能提升空间受限
[0026](1)本发明制备的复合改性酚醛树脂含有季铵盐阳离子基团,可与砂粒表面的负电荷形成静电相互作用;同时树脂分子链上含有大量酯基和酰胺键,可与砂粒表面的羟基形成氢键相互作用;此外,AlN@MOF复合填料通过化学键接枝于树脂分子链上,进一步增强了填料与树脂基体的界面结合。三重机制协同作用,显著提高了固砂剂与砂粒的结合强度。
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional polymer materials technology. More specifically, it relates to a modified resin and its preparation method. Background Technology
[0002] Sand production in oil and gas wells is a common problem during well production. Due to factors such as excessive production pressure differentials and loose rock cementation, formation sand can flow into the wellbore, causing blockages in oil and gas channels, equipment wear, and in severe cases, even well shutdown. Chemical sand control technology is one of the effective means to solve this problem. Among them, phenolic resin has been widely used in the field of sand fixation due to its excellent adhesion, heat resistance, and corrosion resistance.
[0003] Chinese patent application CN120623413A discloses a modified resin sand-fixing agent and its preparation method. The method involves reacting diethanolamine with butyramic acid to prepare a modifier containing ester groups and amide bonds, which is then reacted with bromoacetate phenolic resin to obtain a modified phenolic resin containing quaternary ammonium salt cationic groups. This modified resin enhances the bonding strength between the phenolic resin and the sand particles by forming electrostatic interactions between the quaternary ammonium salt cations and the negative charge on the sand particle surface, while the ester groups and amide bonds form hydrogen bonds with the hydroxyl groups on the sand particle surface. However, this technical solution still has the following shortcomings: (1) the cohesive strength of the resin matrix itself is limited, making it prone to aging and degradation under high temperature and high salt conditions; (2) it lacks inorganic rigid framework support, resulting in insufficient impact resistance and dimensional stability; (3) the multi-point anchoring effect on the sand particle surface suffers from functional group saturation, limiting the potential for performance improvement.
[0004] To overcome the aforementioned shortcomings, existing technologies have attempted to combine inorganic nanomaterials with resins. For example, Chinese patent CN115304784B discloses a boron nitride-modified phenolic resin sand-fixing agent, which reacts a comonomer with boron nitride nanosheets modified with amino groups to obtain a sand-fixing agent with improved temperature resistance and bonding strength. However, this patent requires the additional addition of inorganic nano-boron nitride, and the compressive strength of the cemented rock core remains low. Furthermore, metal-organic frameworks (MOFs) have attracted attention in the field of composite material reinforcement due to their high specific surface area and ordered pore structure, but their application in phenolic resin sand-fixing agents has not yet been reported.
[0005] Based on this, the present invention provides a technical solution that synergistically introduces surface-functionalized aluminum nitride and metal-organic framework into phenolic resin sand-fixing agent to solve the problems of insufficient strength and poor temperature resistance of existing sand-fixing agents. Summary of the Invention
[0006] The technical problem to be solved by this invention is to overcome the defects and deficiencies of the existing technology and provide a modified resin and its preparation method. This invention first prepares a modifier containing ester groups and amide bonds by reacting diethanolamine with butyramic acid; then, it prepares bromoacetate phenolic resin by reacting phenolic resin with bromoacetyl chloride; next, aluminum nitride nanoparticles are acidified and surface-aminated with a silane coupling agent, followed by a hydrothermal reaction with aluminum salt and 2-aminoterephthalic acid to grow an NH2-MIL-53(Al) metal-organic framework in situ on the aluminum nitride surface, obtaining an AlN@MOF composite filler; finally, the bromoacetate phenolic resin, the modifier, and the AlN@MOF composite filler are grafted onto N,N-dimethylformamide to obtain the modified resin. This invention significantly improves the compressive strength and temperature resistance of cemented rock cores through a triple synergistic mechanism: electrostatic adsorption between quaternary ammonium salt cations and sand grain surfaces, hydrogen bonding between ester groups and amide bonds and hydroxyl groups on the sand grain surface, and physical support and impact energy dissipation provided by the AlN@MOF rigid reinforcing phase.
[0007] The purpose of this invention is to provide a method for preparing modified resin.
[0008] Another object of the present invention is to provide a modified resin.
[0009] The above-mentioned objective of this invention is achieved through the following technical solution:
[0010] A method for preparing a modified resin, the method comprising the following steps:
[0011] Step (1): Diethanolamine, butyramic acid, and p-toluenesulfonic acid are dissolved in toluene, nitrogen gas is introduced, the mixture is stirred and reacted, water is added after the reaction is complete, the mixture is shaken and allowed to stand to separate into layers, the organic phase of toluene is extracted and then distilled under reduced pressure and dried to obtain the modifier.
[0012] .
[0013] Step (2): Phenolic resin and triethylamine are mixed in a solvent, nitrogen gas is introduced, and a solution containing bromoacetyl chloride is added dropwise under ice bath conditions. The reaction is stirred and the reaction is completed. After the reaction is completed, the mixture is distilled under reduced pressure, washed with water and petroleum ether, and dried to obtain bromoacetyl phenolic resin.
[0014] Step (3): Disperse aluminum nitride nanoparticles in hydrogen peroxide, treat with a water bath, filter, wash, and dry to obtain pretreated aluminum nitride; then disperse the pretreated aluminum nitride in an ethanol / water mixed solvent, add γ-aminopropyltriethoxysilane KH-550, stir and react under nitrogen protection, filter, wash, and dry to obtain surface-aminated aluminum nitride AlN-NH2; add AlN-NH2, aluminum salt, and 2-aminoterephthalic acid to N,N-dimethylformamide, ultrasonically disperse evenly, solvothermal reaction, filter, wash, and dry to obtain AlN@NH2-MIL-53(Al) composite filler;
[0015] Step (4): Add the modifier obtained in step (1), the bromoacetate phenolic resin obtained in step (2), and the AlN@MOF composite filler obtained in step (3) into N,N-dimethylformamide, stir and react, and after the reaction is complete, distill under reduced pressure, wash with petroleum ether, and dry to obtain the modified resin.
[0016] Preferably, in step (1), the molar ratio of diethanolamine, butyramic acid, and p-toluenesulfonic acid is 1:2.0~2.2:0.06~0.09; the stirring reaction is carried out at 90~110℃ for 12~18h; and the drying is carried out at 80~100℃ for 10~14h.
[0017] Preferably, in step (2), the solvent is selected from at least one of dichloromethane, toluene, or N,N-dimethylformamide; the stirring reaction is carried out at 25~40°C for 6~12 hours.
[0018] Preferably, in step (2), the drying is performed at 80~100℃ for 10~14h; the phenolic hydroxyl group of the phenolic resin is in the range of 7~9mmol / g; based on the number of phenolic hydroxyl groups in the phenolic resin, each 1.0mol of phenolic hydroxyl group corresponds to 0.09~0.20mol of bromoacetyl chloride and 0.10~0.22mol of triethylamine.
[0019] Preferably, in step (3), the aluminum nitride nanoparticles have a particle size of 30~100nm, the amount of KH-550 is 2%~8% of the mass of the pretreated aluminum nitride, the aluminum salt is at least one of aluminum nitrate, aluminum chloride or aluminum sulfate, the molar ratio of the aluminum salt to 2-aminoterephthalic acid is 1:1, and the mass ratio of AlN-NH2 to the aluminum salt is 1:0.5~2.
[0020] Preferably, in step (3), the concentration of hydrogen peroxide is 3~5wt%; the water bath treatment conditions are water bath treatment at 50~70℃ for 2~4h; the drying in step (3) is drying at 80~100℃ for 10~14h; and the volume ratio of ethanol to water is 8:2.
[0021] Preferably, in step (3), the stirring reaction conditions are: stirring reaction at 60~80℃ for 4~8h; the solvothermal reaction conditions are: solvothermal reaction at 120~150℃ for 12~20h.
[0022] Preferably, in step (4), the ratio of the modifier obtained in step (1), the bromoacetic acid phenolic resin obtained in step (2), and the AlN@MOF composite filler obtained in step (3) is 0.06~0.18 mol:100g:3~12g.
[0023] Preferably, the stirring reaction is carried out at 100~120℃ for 36~48h; the drying is carried out at 80~100℃ for 10~14h.
[0024] The modified resin is prepared based on the above-described method for preparing a modified resin.
[0025] The present invention has the following beneficial effects:
[0026] (1) The composite modified phenolic resin prepared in this invention contains quaternary ammonium salt cationic groups, which can form electrostatic interactions with the negative charge on the surface of sand particles; at the same time, the resin molecular chain contains a large number of ester groups and amide bonds, which can form hydrogen bond interactions with the hydroxyl groups on the surface of sand particles; in addition, the AlN@MOF composite filler is grafted onto the resin molecular chain through chemical bonds, which further enhances the interfacial bonding between the filler and the resin matrix. The synergistic effect of the three mechanisms significantly improves the bonding strength between the sand-fixing agent and the sand particles.
[0027] (2) Aluminum nitride nanoparticles, as a rigid reinforcing phase, are uniformly dispersed in the resin matrix and provide physical support; the porous structure of MOF has the effect of reflecting and scattering shock waves, which can effectively dissipate shock energy. The synergistic effect of the two increases the compressive strength of the cemented core by more than 20% compared with the modified resin without inorganic fillers.
[0028] (3) Aluminum nitride is modified by surface amylation with KH-550 to reduce the surface energy of nanoparticles and effectively prevent agglomeration; MOF is further grown in situ on the surface of aluminum nitride to make the surface of composite filler rich in amino groups, which chemically bond with bromoacetate groups to achieve uniform dispersion at the molecular level, thus avoiding the agglomeration and phase separation problems that are easy to occur in physical blending.
[0029] (4) The rigid network of AlN@MOF can inhibit the molecular chain movement of the resin matrix at high temperature and delay the thermo-oxidative aging and degradation; at the same time, the periodic pore structure of MOF can adsorb some salt ions, reduce the erosion of the resin-sand interface by salt, and thus improve the long-term stability of the sand-fixing agent in high temperature and high salt environment.
[0030] (5) Based on the existing modified resin preparation process, the present invention only adds the preparation and blending grafting steps of AlN@MOF composite filler, without the need for complex equipment modification, and is easy to scale up for industrial production. Detailed Implementation
[0031] The present invention will be further illustrated below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.
[0032] Source of raw materials
[0033] Phenolic resin (99% solid content): 1g of resin contains 8.5mmol of phenolic hydroxyl groups; Shandong Chengtian Chemical Co., Ltd.
[0034] Aluminum nitride nanoparticles (50nm particle size): Shanghai Chaowei Nanotechnology Co., Ltd.
[0035] 2-Aminoterephthalic acid (98%): Aladdin Reagent (Shanghai) Co., Ltd.;
[0036] Aluminum nitrate nonahydrate (AR): Sinopharm Chemical Reagent Co., Ltd.;
[0037] γ-aminopropyltriethoxysilane (KH-550, 98%): Nanjing Shuguang Chemical Group;
[0038] N,N-Dimethylformamide (DMF, AR), anhydrous ethanol (AR), toluene (AR), dichloromethane (AR), petroleum ether (AR), acetone (AR): Sinopharm Chemical Reagent Co., Ltd.;
[0039] Diethanolamine (AR), butyramic acid (98%), p-toluenesulfonic acid (AR), triethylamine (AR), bromoacetyl chloride (98%), hexamethylenetetramine (AR): Aladdin Reagents (Shanghai) Co., Ltd.
[0040] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.
[0041] Example 1
[0042] A method for preparing a modified resin includes the following steps:
[0043] Step (1): Dissolve 1 mol diethanolamine, 2.1 mol butyramic acid and 0.08 mol p-toluenesulfonic acid in 150 mL toluene, purge with nitrogen, stir at 100 °C for 16 h, add water after the reaction is complete, shake and let stand to separate the layers, extract, distill the toluene organic phase under reduced pressure, dry at 90 °C for 12 h to obtain the modifier.
[0044] Step (2): Mix 100g of phenolic resin and triethylamine in 300mL of toluene, purge with nitrogen, add 0.4mol / L toluene solution of bromoacetyl chloride dropwise under ice bath conditions, stir and react at 35℃ for 9h, distill under reduced pressure after the reaction is complete, wash with water and petroleum ether, and dry at 90℃ for 12h to obtain bromoacetyl phenolic resin; based on the number of phenolic hydroxyl groups in the phenolic resin, each 1.0mol of phenolic hydroxyl group corresponds to 0.15mol of bromoacetyl chloride and 0.16mol of triethylamine;
[0045] Step (3): 50g of aluminum nitride nanoparticles were dispersed in 100mL of 4wt% hydrogen peroxide and treated in a water bath at 60℃ for 3h. After filtration, washing, and drying at 90℃ for 12h, acidified aluminum nitride was obtained. Then, 50g of the acidified aluminum nitride was dispersed in 150mL of ethanol / water (ethanol to water volume ratio of 8:2) mixed solvent, and 2g of γ-aminopropyltriethoxysilane (KH-550) was added. The mixture was stirred at 70℃ for 6h under nitrogen protection, filtered, washed, and dried at 90℃ for 12h to obtain surface-aminoated aluminum nitride AlN-NH2. 100g of the AlN-NH2, 100g of aluminum nitrate, and 0.469 mol of 2-aminoterephthalic acid were added to 300mL of water. The aluminum nitride nanoparticles were uniformly dispersed in N,N-dimethylformamide by ultrasonication and then subjected to a solvothermal reaction at 140℃ for 16 h. After filtration, washing, and drying at 90℃ for 12 h, AlN@NH2-MIL-53(Al) composite filler was obtained. The particle size of the aluminum nitride nanoparticles was 60 nm.
[0046] Step (4): 0.12 mol of the modifier obtained in step (1), 100g of the bromoacetate phenolic resin obtained in step (2) and 8g of the AlN@MOF composite filler obtained in step (3) were added to 300mL of N,N-dimethylformamide and stirred at 110℃ for 40h. After the reaction was completed, the mixture was distilled under reduced pressure, washed with petroleum ether, and dried at 90℃ for 12h to obtain the modified resin.
[0047] Example 2
[0048] A method for preparing a modified resin includes the following steps:
[0049] Step (1): Dissolve 1 mol diethanolamine, 2.2 mol butyramic acid and 0.09 mol p-toluenesulfonic acid in 150 mL toluene, purge with nitrogen, stir at 110 °C for 12 h, add water after the reaction is complete, shake and let stand to separate the layers, extract, distill the toluene organic phase under reduced pressure, dry at 100 °C for 10 h to obtain the modifier.
[0050] Step (2): Mix 100g of phenolic resin and triethylamine in 300mL of dichloromethane, purge with nitrogen, add 0.4mol / L toluene solution of bromoacetyl chloride dropwise under ice bath conditions, stir and react at 40℃ for 6h, after the reaction is complete, distill under reduced pressure, wash with water and petroleum ether, dry at 100℃ for 10h to obtain bromoacetyl phenolic resin; based on the number of phenolic hydroxyl groups in the phenolic resin, each 1.0mol of phenolic hydroxyl group corresponds to 0.20mol of bromoacetyl chloride and 0.10mol of triethylamine;
[0051] Step (3): 50g of aluminum nitride nanoparticles were dispersed in 100mL of 4wt% hydrogen peroxide and treated in a water bath at 60℃ for 3h. After filtration, washing, and drying at 90℃ for 12h, acidified aluminum nitride was obtained. Then, 50g of the acidified aluminum nitride was dispersed in 150mL of ethanol / water (ethanol to water volume ratio of 8:2) mixed solvent, and 2g of γ-aminopropyltriethoxysilane (KH-550) was added. The mixture was stirred at 70℃ for 6h under nitrogen protection, filtered, washed, and dried at 90℃ for 12h to obtain surface-aminated aluminum nitride AlN-NH2. 100g of AlN-NH2, 200g of aluminum chloride, and 1.5 mol of 2-aminoterephthalic acid were added to 300mL of water. The aluminum nitride nanoparticles were uniformly dispersed in N,N-dimethylformamide by ultrasonication, and then subjected to a solvothermal reaction at 150℃ for 12 h. After filtration, washing, and drying at 100℃ for 10 h, AlN@NH2-MIL-53(Al) composite filler was obtained. The particle size of the aluminum nitride nanoparticles was 100 nm.
[0052] Step (4): Add 0.18 mol of the modifier obtained in step (1), 100g of the bromoacetate phenolic resin obtained in step (2) and 3g of the AlN@MOF composite filler obtained in step (3) to 300mL of N,N-dimethylformamide, stir and react at 120℃ for 36h, after the reaction is completed, distill under reduced pressure, wash with petroleum ether, and dry at 100℃ for 10h to obtain the modified resin.
[0053] Example 3
[0054] A method for preparing a modified resin includes the following steps:
[0055] Step (1): Dissolve 1 mol diethanolamine, 2.0 mol butyramic acid and 0.06 mol p-toluenesulfonic acid in 150 mL toluene, purge with nitrogen, stir at 90 °C for 18 h, add water after the reaction is complete, shake and let stand to separate the layers, extract, distill the toluene organic phase under reduced pressure, dry at 80 °C for 14 h to obtain the modifier.
[0056] Step (2): Mix 100g of phenolic resin and triethylamine in 300mL of N,N-dimethylformamide, purge with nitrogen, add 0.4mol / L toluene solution of bromoacetyl chloride dropwise under ice bath conditions, stir and react at 25℃ for 12h, after the reaction is complete, distill under reduced pressure, wash with water and petroleum ether, and dry at 80℃ for 14h to obtain bromoacetyl phenolic resin; based on the number of phenolic hydroxyl groups in the phenolic resin, each 1.0mol of phenolic hydroxyl group corresponds to 0.09mol of bromoacetyl chloride and 0.22mol of triethylamine;
[0057] Step (3): 50g of aluminum nitride nanoparticles were dispersed in 100mL of 4wt% hydrogen peroxide and treated in a water bath at 60℃ for 3h. After filtration, washing, and drying at 90℃ for 12h, acidified aluminum nitride was obtained. Then, 50g of the acidified aluminum nitride was dispersed in 150mL of ethanol / water (ethanol to water volume ratio of 8:2) mixed solvent, and 2g of γ-aminopropyltriethoxysilane (KH-550) was added. The mixture was stirred at 70℃ for 6h under nitrogen protection, filtered, washed, and dried at 90℃ for 12h to obtain surface-aminoated aluminum nitride AlN-NH2. 100g of the AlN-NH2, 50g of aluminum sulfate, and 0.146 mol of 2-aminoterephthalic acid were added to 300mL of water. The aluminum nitride nanoparticles were uniformly dispersed in N,N-dimethylformamide by ultrasonication and then subjected to a solvothermal reaction at 120℃ for 20 h. After filtration, washing, and drying at 80℃ for 14 h, AlN@NH2-MIL-53(Al) composite filler was obtained. The particle size of the aluminum nitride nanoparticles was 30 nm.
[0058] Step (4): Add 0.06 mol of the modifier obtained in step (1), 100g of the bromoacetate phenolic resin obtained in step (2) and 12g of the AlN@MOF composite filler obtained in step (3) to 300mL of N,N-dimethylformamide, stir and react at 100℃ for 48h, after the reaction is completed, distill under reduced pressure, wash with petroleum ether, and dry at 80℃ for 14h to obtain the modified resin.
[0059] Comparative Example 1
[0060] The modifier and bromoacetate phenolic resin were prepared according to steps (1) and (2) of Example 1, and then the reaction was carried out according to step (4) to obtain the modified resin.
[0061] Comparative Example 2
[0062] The modified resin was prepared according to the method of Example 1, except that an equal amount of aluminum nitride nanoparticles were used to replace the AlN@NH2-MIL-53(Al) composite filler, and other conditions were the same as in Example 1.
[0063] Comparative Example 3
[0064] The modified resin was prepared according to the method of Example 1, except that an equal amount of surface-aminated aluminum nitride AlN-NH2 was used instead of AlN@NH2-MIL-53(Al) composite filler, and other conditions were the same as in Example 1.
[0065] Comparative Example 4
[0066] The modified resin was prepared according to the method of Example 1, except that an equal amount of NH2-MIL-53(Al) was used instead of AlN@NH2-MIL-53(Al) composite filler, while other conditions were the same as in Example 1. The preparation process of NH2-MIL-53(Al) was as follows: 100g of aluminum nitrate and 0.469 mol of 2-aminoterephthalic acid were added to 300mL of N,N-dimethylformamide, ultrasonically dispersed, and reacted solvothermically at 140℃ for 16h. After filtration, washing, and drying at 90℃ for 12h, NH2-MIL-53(Al) was obtained.
[0067] The sand-fixing performance test results are shown in Table 1.
[0068] 0.6 kg of the modified resins from Examples 1-3 and Comparative Examples 1-4 were added separately to 500 mL of acetone along with hexamethylenetetramine (8% of the modified resin mass), and stirred until the modified resins dissolved. 10 kg of sand (crushed and sieved through a 40-mesh sieve, simulating formation sand) was added and thoroughly mixed until homogeneous. The mixture was dried at 60°C to constant weight to obtain resin-coated sand. The mixture was poured into a 3 cm × 3 cm × 3 cm mold, compacted, and cured at 120°C for 24 h. After cooling to room temperature, it was left to stand for 72 h before demolding to obtain cemented core samples.
[0069] Compressive strength test
[0070] The prepared cemented core samples were placed in a universal testing machine (Shenzhen Xin Sansi Materials Testing Co., Ltd., CMT series) and continuously pressurized at a loading rate of 0.5 mm / min until the samples were crushed. The maximum pressure value at the moment of crushing was recorded as the compressive strength. Five parallel samples were tested in each group, and the average value was taken as the final result.
[0071] Temperature resistance test
[0072] The solidified cemented rock core sample was placed in a high-temperature aging chamber and aged at 150°C for 72 hours. After cooling to room temperature, the compressive strength was tested according to the above method, and the strength retention rate was calculated as (strength after aging / initial strength × 100%).
[0073] Table 1
[0074]
[0075] As shown in Table 1, compared with Comparative Example 1, the initial compressive strength of Examples 1-3 was significantly higher than that of Comparative Example 1. This indicates that the modified resin of the present invention effectively improves the bonding strength of the sand-fixing agent through the triple synergistic effect of quaternary ammonium salt cations, ester / amide bonds, and AlN@MOF reinforcing phase.
[0076] (2) Comparison between Example 1 and Comparative Example 2: Comparative Example 2 used unfunctionalized aluminum nitride for direct physical mixing, and the compressive strength was much lower than that of Example 1. This indicates that unfunctionalized nano-aluminum nitride is prone to agglomeration in the resin matrix, resulting in poor interfacial bonding and inability to effectively transfer load; while the present invention achieves uniform dispersion and strong interfacial bonding at the molecular level by surface amination of KH-550 and in-situ growth of MOF on its surface, making the surface of the composite filler rich in reactive amino groups, which chemically bond with bromoacetate groups.
[0077] (3) Comparison between Example 1 and Comparative Example 3: Comparative Example 3 used AlN-NH2 (without MOF) instead of AlN@MOF, and its compressive strength was lower than that of Example 1. This proves that the introduction of MOF is not a simple additive effect, but rather reflects, scatters and dissipates impact energy through the porous structure of MOF. At the same time, the MOF layer increases the number of amino sites that can react with the resin, enhances the interfacial bonding density, and produces a reinforcing effect that exceeds that of AlN alone.
[0078] (4) Comparison of Example 1 and Comparative Example 4: Comparative Example 4 used NH2-MIL-53(Al) (without AlN) instead of AlN@MOF, and its compressive strength was still lower than that of Example 1. This shows that aluminum nitride, as a rigid reinforcing phase, provides indispensable cohesive strength support. Although MOF can improve interfacial bonding, it lacks the physical support of a rigid core, and its reinforcing effect is limited. There is a synergistic reinforcing effect between AlN and MOF.
[0079] (5) Temperature resistance analysis: The strength retention rate of Examples 1-3 after aging at 150℃ for 72h was higher than 90%, which indicates that AlN@MOF composite filler effectively inhibited the movement of resin molecular chains and thermo-oxidative degradation at high temperature by constructing an organic-inorganic interpenetrating network, and significantly improved the temperature resistance of modified resin.
[0080] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for preparing a modified resin, characterized in that: The preparation method includes the following steps: Step (1): Diethanolamine, butyramic acid, and p-toluenesulfonic acid are dissolved in toluene, nitrogen gas is introduced, the mixture is stirred and reacted, water is added after the reaction is complete, the mixture is shaken and allowed to stand to separate into layers, the organic phase of toluene is extracted and then distilled under reduced pressure and dried to obtain the modifier. Step (2): Phenolic resin and triethylamine are mixed in a solvent, nitrogen gas is introduced, and a solution containing bromoacetyl chloride is added dropwise under ice bath conditions. The reaction is stirred and the reaction is completed. After the reaction is completed, the mixture is distilled under reduced pressure, washed with water and petroleum ether, and dried to obtain bromoacetyl phenolic resin. Step (3): Disperse aluminum nitride nanoparticles in hydrogen peroxide, treat with a water bath, filter, wash, and dry to obtain pretreated aluminum nitride; then disperse the pretreated aluminum nitride in an ethanol / water mixed solvent, add γ-aminopropyltriethoxysilane KH-550, stir and react under nitrogen protection, filter, wash, and dry to obtain surface-aminated aluminum nitride AlN-NH2; add AlN-NH2, aluminum salt, and 2-aminoterephthalic acid to N,N-dimethylformamide, ultrasonically disperse evenly, solvothermal reaction, filter, wash, and dry to obtain AlN@NH2-MIL-53(Al) composite filler; Step (4): Add the modifier obtained in step (1), the bromoacetate phenolic resin obtained in step (2), and the AlN@MOF composite filler obtained in step (3) into N,N-dimethylformamide, stir and react, and after the reaction is complete, distill under reduced pressure, wash with petroleum ether, and dry to obtain the modified resin.
2. The method for preparing a modified resin according to claim 1, characterized in that: In step (1), the molar ratio of diethanolamine, butyramic acid, and p-toluenesulfonic acid is 1:2.0~2.2:0.06~0.09; the stirring reaction is carried out at 90~110℃ for 12~18h; and the drying is carried out at 80~100℃ for 10~14h.
3. The method for preparing a modified resin according to claim 1, characterized in that: In step (2), the solvent is selected from at least one of dichloromethane, toluene or N,N-dimethylformamide; the stirring reaction is carried out at 25~40℃ for 6~12h.
4. A method for preparing a modified resin according to claim 1 or 3, characterized in that: In step (2), the drying is performed at 80~100℃ for 10~14h; based on the number of phenolic hydroxyl groups in the phenolic resin, each 1.0 mol of phenolic hydroxyl group corresponds to 0.09~0.20 mol of bromoacetyl chloride and 0.10~0.22 mol of triethylamine.
5. The method for preparing a modified resin according to claim 1, characterized in that: In step (3), the aluminum nitride nanoparticles have a particle size of 30~100nm, the amount of KH-550 is 2%~8% of the mass of the pretreated aluminum nitride, the aluminum salt is at least one of aluminum nitrate, aluminum chloride or aluminum sulfate, the molar ratio of the aluminum salt to 2-aminoterephthalic acid is 1:1, and the mass ratio of AlN-NH2 to the aluminum salt is 1:0.5~2.
6. A method for preparing a modified resin according to claim 1 or 5, characterized in that: In step (3), the concentration of hydrogen peroxide is 3-5 wt%; the water bath treatment conditions are 50-70℃ for 2-4 hours; the drying in step (3) is 80-100℃ for 10-14 hours; and the volume ratio of ethanol to water is 8:
2.
7. A method for preparing a modified resin according to claim 1 or 5, characterized in that: In step (3), the stirring reaction conditions are: stirring reaction at 60~80℃ for 4~8h; the solvothermal reaction conditions are: solvothermal reaction at 120~150℃ for 12~20h.
8. The method for preparing a modified resin according to claim 1, characterized in that: In step (4), the ratio of the modifier obtained in step (1), the bromoacetic acid phenolic resin obtained in step (2), and the AlN@MOF composite filler obtained in step (3) is 0.06~0.18 mol:100g:3~12g.
9. A method for preparing a modified resin according to claim 1 or 8, characterized in that: The stirring reaction conditions are 100~120℃ for 36~48h; the drying conditions are 80~100℃ for 10~14h.
10. A modified resin prepared by a method for preparing a modified resin according to any one of claims 1-9.
Citation Information
Patent Citations
Boron nitride modified phenolic resin sand-resistant agent, its preparation method and uses
CN115304784B
Modified resin as well as preparation method and application thereof
CN120623413A
